Cybersecurity Frameworks for Autonomous Vehicle Systems: Safeguarding Onboard Systems, Communication Networks, and Data Privacy in Smart City Ecosystems (Internet of Things and Edge Computing Journal, 2024)
In the rapidly evolving landscape of transportation technology, the advent of autonomous vehicles (AVs) promises transformative benefits in terms of safety, efficiency, and mobility. However, with this promise comes the critical imperative of ensuring robust cybersecurity measures to safeguard AVs against potential threats and vulnerabilities. This research article delves into the development of comprehensive cybersecurity frameworks tailored specifically to autonomous vehicle systems, with a particular focus on securing onboard systems, communication networks, and data privacy within smart city ecosystems.The introduction contextualizes the significance of AV technology and underscores the pivotal role of cybersecurity in ensuring its safe integration into smart city environments. Recognizing the multifaceted nature of cybersecurity challenges facing AVs, the research delineates the scope of the investigation, aiming to provide actionable insights and strategies for mitigating risks across various domains.The first section examines the challenges inherent in securing autonomous vehicle systems, identifying vulnerabilities within onboard components such as sensors, controllers, and actuators. It further elucidates the risks posed by potential cyberattacks targeting communication networks connecting AVs to each other and to urban infrastructure. Additionally, the section highlights the privacy concerns associated with the collection, storage, and sharing of sensitive data generated by AVs.Building upon an analysis of existing cybersecurity frameworks applicable to AVs, the research proposes a comprehensive cybersecurity framework tailored to the unique requirements of autonomous vehicles operating within smart city environments. Drawing from established principles of cybersecurity and risk management, the framework integrates proactive measures such as threat modeling, risk assessment, and mitigation strategies, with a focus on real-time monitoring and incident response capabilities.Subsequent sections delve into specific strategies for securing onboard systems, encompassing authentication mechanisms, access control protocols, and intrusion detection/prevention systems. Moreover, the research explores encryption techniques and network security measures to protect communication networks, emphasizing the importance of resilience against emerging threats such as denial-of-service attacks.Addressing the paramount concern of data privacy, the framework advocates for the minimization of data collection, adoption of anonymization techniques, and adherence to relevant privacy regulations to safeguard user privacy in AV operations. Furthermore, the research elucidates the challenges and opportunities associated with integrating AVs into existing smart city ecosystems, emphasizing the need for seamless coordination with urban mobility systems and collaboration with IoT devices and platforms.By analyzing case studies and practical implementations of cybersecurity frameworks in autonomous vehicle fleets, the research offers valuable insights and best practices derived from real-world deployments. Finally, the conclusion summarizes key findings and outlines future research directions aimed at further enhancing the cybersecurity posture of autonomous vehicles in smart city environments.This research article provides a comprehensive examination of cybersecurity frameworks for autonomous vehicle systems, offering actionable strategies and insights to address the evolving challenges of securing AVs within smart city ecosystems.